5-(3-Fluorophenyl)-1,3,4-thiadiazol-2-amine - Wang, Yao (International Union of Crystallography, 2009)
The title compound, C(8)H(6)FN(3)S, was synthesized by the reaction of 3-fluorobenzoic acid and thiosemicarbazide. The dihedral angle between the planes of the thiadiazole and benzene rings is 37.3 (2)°. In the structure, two crystallographically independent molecules form a centrosymmetric dimer, in which two intermolecular N—H⋯N hydrogen bonds generate an R (2) (2)(8) motif.